Analysis of Competence and Work Experience on Employee Performance with Incentives as Intervening Variables PT Shopee International Indonesia - Eddy Prastyawan; Sarsono; Ida Aryati DPW (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The research aims to examineRegarding the Role of Competence and Work Experience on Employee Performance with Incentives as an Intervening Variable (Study at PT Shopee International Indonesia Surakarta Branch)using the Purposive Sampling method as a sampling technique. In this context, researchers select samples that are considered to represent certain characteristics that are relevant to the research objectives. Of the 114 sample data above, consisting of employees from PT Shopee International Surakarta branch from various departments such as Operational (50 employees), Quality Assurance (54 employees), and Human Resources (10 employees), with permanent employee status and have a work period of the same or more than 2 years. The variables used in this study are as follows: The Dependent Variable (Y) in this study is Employee Performance, the Independent Variable (X) in this study is Competence (X1) and Work Experience (X2) and the Intervening Variable in this study is Incentive (Z). Testing in this study was carried out using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS) which is based on components or variants.Competence and Work Experience have a direct effect on the performance of employees of PT Shopee International Indonesia, Surakarta branch. The statement that incentive variables have an effect on performance and also mediate the relationship between competence and work experience on performance shows that financial incentives play an important role in improving employee performance. Keywords: Employee Performance, Competence, Work Experience, Incentives